Sustainable Educational Facilities Management as a Strategic Organizational Capability for Enhancing Academic Service Effectiveness in Indonesian Madrasahs - Abu Siri; Shovia Khomiyatul Aly; Roibeh; Misdin Arifin Hm (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2026)
Educational facilities management has traditionally been viewed as an operational function, with limited attention given to its strategic contribution to academic service effectiveness in Islamic educational institutions. This study aims to examine the influence of Sustainable Educational Facilities Management (SEFM) on Academic Service Effectiveness (ASE) in Indonesian madrasahs while extending the Resource-Based View (RBV) and Sustainable Management Theory. A quantitative explanatory research design with a cross-sectional survey was employed. Data were collected from 120 teachers and educational personnel at MI Manbaul Ulum Lantek Barat, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Sustainable Educational Facilities Management has a positive and significant effect on Academic Service Effectiveness, indicating that sustainability-oriented planning, procurement, utilization, maintenance, evaluation, and governance strengthen institutional capability to deliver effective academic services. This study reconceptualizes SEFM as a strategic organizational capability rather than merely an administrative function, thereby extending educational management literature through the integration of sustainability, strategic resource management, and academic service effectiveness. The findings also provide practical guidance for madrasah leaders and policymakers in strengthening sustainability-oriented educational governance to improve institutional quality and long-term educational performance.